Volumetric investigation of brain regions in patients with conversion disorder - Atmaca, Murad; Aydin, Ayse; Tezcan, Ertan; Poyraz, A. Kursad; Kara, Bilge (Pergamon-Elsevier Science Ltd, 2006)
Preliminary evidence revealed a decrease of regional cerebral blood flow in the thalamus and basal ganglia contralateral to the deficit and suggested that hysterical conversion deficits might entail a functional disorder in striatothalamocortical circuits. However, there is no systematic structural magnetic resonance imaging (MRI) study in the literature in patients with conversion disorder (CD). Therefore, we aimed to perform structural MRI to evaluate the brain regions of interest in first applying patients with CD. Morphometric MRI was used to compare regional brain volumes in ten women with CD and same number of healthy comparison subjects. Intracranial volume (ICV), whole brain volume, gray and white matter volumes did not differ between the patient and control groups. Patients with CD had significantly smaller mean volumes of the left caudate nucleus, lentiform nucleus (p < 0.01 for caudate nucleus and p < 0.05 for lentiform nucleus) and right caudate nucleus and lentiform nucleus (p < 0.05 for both structures). In patients, the right thalamus was significantly smaller, and the left thalamus rendered to be smaller compared to healthy controls. Age at onset showed a significant relation with left caudate, and a near-significant trend with right thalamus volumes. In conclusion, our findings suggest that patients with CD have significantly smaller mean volumes of the left and right basal ganglia and smaller tight thalamus, with a trend toward to smaller left thalamus compared to healthy controls and that these findings provide novel constraints for a modern psychobiological theory of hysteria. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: basal ganglia; conversion disorder; MRI; structural; thalamus; volume